TATA KELOLA MODEL IT GOVERNANCE PADA LAYANAN AKADEMIK MENGGUNAKAN FRAMEWORK COBIT 4.1 PADA DOMAIN (DELIVERY AND SUPPORT) DAN (MONITORING AND EVALUATION) - Hermawaty Hermawaty (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2017)
The role of academic information system in the High School of Information and Computer Management "AMIK BANDUNG" (STMIK "AMIKBANDUNG") is now implemented, but has not been managed using structured approaches and methods, so there is difficulty in measuring the role of information technology to achieve institutional goals Effective and efficient. The research methodology used in this research is data collection in the form of observation, interview and questionnaire distribution. IT Governance (Information Technology Governance) is an important factor for an organization in the institution in utilizing information technology, which will provide assurance that the use of informationtechnology aligned with organizational goals. In this study using COBIT framework 4.1. Based on consideration, that COBIT 4.1. Made using IT standards as a reference so that the alignment of IT development with the goal of the institution is relatively more secure. The tool used to map the position of the information system process is to use a questionnaire. Questionnaires were made using priority scale measurement techniques.From the results of this study obtained that the role of IT to institutions in the scale of model maturity is on scale 4 (managed), meaning that institutions can measure and monitor the existing procedures so easily addressed if there is deviation. The conclusion of this research is that the result of IT process mapping is obtained from the description that the institutional position for each process is on average at the fourth level of maturity that is regulated, meaning that IT implementation in the institution has been following a regular pattern, but shoul be supervised and evaluate from each process.